Construção de uma biblioteca de anticorpos monoclonais apresentados em fagos para seleção e caracterização de scFv ligante a proteínas intestinais de Diatraea saccharalis - Nascimento, Rafael (2009)
The sugarcane borer, Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae), is the most important insect pest of sugarcane grown in Brazil and others localities in the Americas, causing stalk damage to sugarcane plants which results in loss of efficiency in both sugar and alcohol production. The extensive damage caused by this pest in the sugarcane cultivation and its difficult control by conventional insecticides justify the search for new strategies that can help to reduce the use of harmful chemicals to humans and the environment. In order to generate new molecules with insecticidal activity against the sugarcane borer, the present work aimed to build a scFv antibody fragment library through Phage Display technology for selection and characterization of molecules with binding properties against D. saccharalis larval midgut proteins. The methodology used was efficient, allowing the selection of a scFv with immunoreactivity for the insect intestinal epithelium and with potential insecticidal activity.